MUDANÇAS PALEOAMBIENTAIS E PALEOCLIMÁTICASDURANTE O QUATERNÁRIO TARDIO NA SERRA DO CABRAL,MINAS GERAIS, BRASIL, POR MEIO DE ANÁLISESPALINOLÓGICAS E DE ISÓTOPOS C E N - Makenia Oliveira Soares Gomes (2017)
The main paleovegetation and paleoclimatic changes over the last 21,000 years BP (Pleistocene-Holocene),in the Serra do Cabral, northern Minas Gerais state, were reconstructed based on pollen and stable isotope (Cand N) analyses of the Palm Swamps known as Água Fria and Carrasco da Raposa, located in the Serra doCabral State Park (PESC). The results suggest two phases of climate change and vegetation in the Água FriaPalm Swamp (VAF I and VAF II). In the former, between 20,500 and 3,650 calibrated years before thepresent (cal yr BP), a lower humidity and absence of Mauritia flexuosa were observed. From ~3,650 cal yrBP to the present (VAF II), the climate was more humid, similar to that of the present day. Concerning theplant physiognomy evolution, a succession of vegetation was verified, including a mosaic of Cerradograssland formations, Campo Úmido, forest elements as trees and shrubs in the base until the median portionof the core sample. Toward the top, there was an increase of the typical elements of Campo Úmido and theappearance of the Palm Swamp, i.e. occurrence of the buriti palm Mauritia flexuosa. The isotopic data of Cand N indicated that between 20,500 and 3,650 cal yr BP there was a probable mixture of C3 and C4 plantsas source of the sedimentary organic matter, but with the predominance of C3 plants. Values of 13C variedbetween -22.09 and -20.04. The C/N ratio presented a mean of 36.3 in VAF I, and suggested thepredominance of organic matter derived from terrestrial plants, which was corroborated by the 15N around6. In VAF II, from 3,650 cal yr BP to present day, there was a decrease in the C/N values, with 15 in theuppermost sample. These results confirmed the tendency of increasing humidity and greater freshwaterphytoplankton influence in the composition of the Palm Swamp sedimentary organic matter for this timeinterval. In the Carrasco da Raposa Palm swamp, three phases were identified. The lower one is here referredto as VCR I (from 21,150 to 18,850 cal yr BP), during which the climate was colder and less humid than inother phases, probably due to the influence of the Last Glacial Maximum. In VCR II (from18,850 to 3,550cal yr BP), the climate became warmer and wetter than in the previous phase, and from 3,550 cal yr BP untilthe present day (VCR III), the Palm Swamp appeared at climate conditions similar to the current one. Theseresults are similar to those observed in the Água Fria Palm swamp. Concerning the plant physiognomychanges, a succession of vegetation was observed, with predominance of Cerrado grassland formationsassociated with traces of forest formations in the base (VCR I), Campo Sujo Úmido and Campo Rupestreassociated to typical Cerrado forest elements in VCR II; and the establishment of Palm Swamp in VCR III(3,550 cal yr BP and its expansion after 1,650 cal yr BP. as in the Água Fria Palm swamp. The isotopic dataof C and N suggests that there was a probable mixture of plants C3 and C4 as a source of the sedimentaryorganic matter at VCR I and VCR II, but with the predominance of plants C3. In this case, 13C rangedbetween -24 and -21.5. The values of C/N (from 1.5 to 11.5) indicate the predominance of organicmatter derived from phytoplankton and the values of 15N (3.5 to ~ 1.0) may be associated with amixture of organic matter from freshwater phytoplankton and land plants. From 3,550 cal yr BP until thepresent (VCR III), there was a decrease in the values of C/N (1.5 to ~6), which confirmed the presence offlooded environment with greater freshwater phytoplankton influence in the composition of the sedimentaryorganic matter.